An Evaluation of Some Mechanical Properties of Autopolymerizing Acrylic Resin with the Modified One after Changing the Curing Environment: (In vitro Study) - Intisar J Ismail (College of Dentistry/ University of Baghdad, 2015)
Background: Studying and investigating the transverse strength(Ts), impact strength(Is), hardness (Hr) and surface roughness(Ra) of conventional and modified autopolymerizing acrylic resin with different weight percentages of biopolymer kraftlignin, after curing in different water temperatures; 40°C and 80°C. Material and Methods: Standard acrylic specimens were fabricated according to ADA specification No.12 for transverse strength, ISO 179 was used for impact testing, Shore D for hardness and profilometerfor surface roughness. The material lignin first dispersed in the monomer, then the powder PMMA is immediately added. Ligninadded in different weight percentages. Then cured using pressure pot (Ivomet) in two temperatures;40°C and 80°C under 2 bar pressure, for 30 minutes.Atotal of 144samples were prepared for this study. Ts, Is, Ra, and Hr were tested, by using Instron universal testing machine, charpy impact tester, shore D tester, and profilometer respectively. Results: The transverse strength increased in both the conventional and modified onewhen compared with that cured in air. The addition of 0.5wt% lignin gave the higher effect (78.0017MPa) with highly significant difference found between groups at 40°C polymerizing temperature. While the impact strength in both temperatures in the modified resin revealed increased results than conventional one, 1.25wt% of kraft lignin gave the highest value (12.7355KJ/m2) with highly significant differences found between groups at 80°C polymerizing temperature. Hardness and surface roughness showed also highly significant differences found between groups at 40°C polymerizing temperature, all the groups had increased Hr. than the control one (78.95), while the Ra. decreased for 1.0% ,1.25,1.50 and 1.75 wt% lignin content to (0.26,0.10,0.063, 0.12µm) respectively in 40°C polymerizing temperature, the lowest value present in 1.75 wt% lignin (0.05 µm) at 80°Cpolymerizing temperature. Conclusions: It seems that increasing the polymerizing temperature to 40°C had a positive effect on the mechanical properties of autopolymerizing acrylic resin and the one enforced by kraft lignin biopolymer in low percentages. Increasing the polymerizing temperature to 80°C will doesn't have much positive effect but it doesn't deteriorate the mechanical properties. However, when submitted to increasing the temperature to 80°C, specimens showed a significant increase in impact strength.